AI Anxiety and Workforce Resilience Through ESG Social Responsibility and Adult Education - Nagyné Náray, Szilvia Sarkadi; Macher, Gergely Zoltán (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The rapid integration of Artificial Intelligence (abbreviation: AI) is driving a profound industrial transformation, yet it simultaneously generates considerable anxiety among employees, posing risks to sustainable organizational performance. This paper examines AI-related anxiety within the Hungarian labour market and explores mitigation strategies through the lens of the ESG Social pillar. Adopting a mixed-method approach, combining online surveys to assess learning self-efficacy with qualitative interviews, the research investigates the intersection of technological disruption and human capital management. Findings demonstrate that psychological safety and targeted adult education function not merely as HR instruments but as essential governance mechanisms. Moreover, the data highlight that transparent communication regarding AI deployment alleviates uncertainty and fosters a resilient organizational climate conducive to continuous innovation. The paper argues that navigating AI transformation successfully requires a paradigm shift in management. Sustainable governance must prioritize the human dimension by cultivating trust-based environments.